2022
DOI: 10.3390/jcm11216318
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Dental Malocclusion: An Otolaryngologic Perspective

Abstract: Allergic rhinitis (AR), which is a major cause of upper airway obstruction, may affect the development of the dental malocclusion. This retrospective study was aimed to investigate association between AR and dental malocclusion in otolaryngologic perspectives. Methods: Patients (n = 217) referred to the otolaryngology department before initiating orthodontic treatment were recruited. The frequency and severity of AR symptoms, sinonasal outcome test (SNOT-22) scores, physical examination findings, acoustic rhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Even though the current risk of contagion is significantly decreased thanks to vaccination and protective measures, an increased number of procedures in the waiting list accounting for 66.9%, as reported by our data, is worrying and could keep growing without the application of an integrated strategy. In fact, even a common diagnosis of adenotonsillar disease can lead to several comorbidities, such as cardiopulmonary complications, deficit of attention and dental malocclusions [9][10][11] . Medical management of severe obstructive sleep apnoea during the COVID-19 pandemic, including continuous positive airway pressure therapy in severe cases, showed that this kind of treatment is poorly tolerated, and that surgery remains the gold standard 12 .…”
Section: Management Of Adenotonsillar Diseasementioning
confidence: 99%
“…Even though the current risk of contagion is significantly decreased thanks to vaccination and protective measures, an increased number of procedures in the waiting list accounting for 66.9%, as reported by our data, is worrying and could keep growing without the application of an integrated strategy. In fact, even a common diagnosis of adenotonsillar disease can lead to several comorbidities, such as cardiopulmonary complications, deficit of attention and dental malocclusions [9][10][11] . Medical management of severe obstructive sleep apnoea during the COVID-19 pandemic, including continuous positive airway pressure therapy in severe cases, showed that this kind of treatment is poorly tolerated, and that surgery remains the gold standard 12 .…”
Section: Management Of Adenotonsillar Diseasementioning
confidence: 99%